EFFECTS OF TRADE FLOW LIBERALIZATION: CASE OF ASEAN, NAFTA & MERCOSUR - Hasan Mahmutović; Alem Merdić (Human Research in Rehabilitation, 2018)
An important factor and the inescapable link of the globalization process are economic integrations, which by the liberalization of trade flows contributes significantly to the interconnection of countries, thus directly affecting the enhancement of the value of macroeconomic parameters at the level of the formed integration. The aim of this paper is to examine the effects of economic integration on the example of ASEAN, NAFTA and MERCOSUR integration, which, along with the European Union, represent the most relevant integrations in the world. The analysis showed, as a consequence of the integration, increased volume of trade exchange, increased FDI level and achieved real economic growth on the level of integration. However, the analysis has shown, in particular in the ASEAN area, that there is still a problem of uneven distribution of income and fairer implementation of regional policy, in order to integrate growth generated into the development of less developed areas.